ANALISIS TINGKAT EFISIENSI PERBANKAN SYARIAH PROVINSI JAMBI TAHUN 2010 - 2014 - Intan, Intan (e-Journal Perdagangan Industri dan Moneter, 2016)
The purpose of this research is to calculate the great value and analyze the efficiency and performance efficiency of Islamic banking in Jambi Province. This study usesdescriptive analysis method type of comparative where the author uses secondary data to support this study by looking at the development and then analyze it in accordance with the data available. The results showed that the average efficiency of Islamic banking in the whole province of Jambi in 2010-2014 is considered efficient by the achievement of 61.61% since the rate is located at position <93.52 or in a standard measure of efficiency if it is close to zero or (<100 ) is calculated as a percentage then considered efficient. this suggests that the growth of operating expenses to operating income has experienced a significant balance. In addition, the development of Islamic Banking performance in Jambi Province from 2010 to 2014, in the times of the formation and establishment showed a good performance. Including Asset, financing, deposits, FDR, and the NPF